Status of the TORCH time-of-flight project - Harnew, N; Bhasin, S; Blake, T; Brook, N; Conneely, T; Cussans, D; Van Dijk, M; Forty, R; Frei, C; Gabriel, E; Gao, R; Gershon, T; et al. (Elsevier, 2018)
TORCH is a time-of-flight detector, designed to provide charged π∕K particle identification up to a momentum of 10GeV/c for a 10m flight path. To achieve this level of performance, a time resolution of 15 ps per incident particle is required. TORCH uses a plane of quartz of 1 cm thickness as a source of Cherenkov photons, which are then focussed onto square Micro-Channel Plate Photomultipliers (MCP-PMTs) of active area 53 × 53mm2, segmented into 8 × 128 pixels equivalent. A small-scale TORCH demonstrator with a customised MCP-PMT and associated readout electronics has been successfully operated in a 5GeV/c mixed pion/proton beam at the CERN PS facility. Preliminary results indicate that a single-photon resolution better than 100ps can be achieved. The expected performance of a full-scale TORCH detector for the Upgrade II of the LHCb experiment is also discussed.